Analysis Of The Application Of Law N0. 11 Of 2020 Concerning Job Creation On Criminology Of Subsidized Fuel Oil Sellers In Dedai District, Sintang Regency - Urmilawati, Ully; Saly, Jeane Neltje (International Journal Labs, 2023)
This study aims to analyze what factors cause the perpetrators of the sale of subsidized fuel oil (BBM) not to supply or distribute it on target, and to analyze the conformity of Law No. 11 of 2020 concerning copyright work on the criminology of sellers of subsidized fuel oil, and find out how efforts or actions that can be taken by law enforcement against sellers of subsidized fuel oil that are not on target. This study uses empirical legal research in which a legal research method functions to be able to see law in a real sense by examining how law works in a community environment. The results of this study indicate that the factors behind the actions of the seller of subsidized fuel oil in Dedai District, Sintang Regency, namely the implementation of the sale of subsidized fuel oil occurred inaccuracy due to a game from the gas station by putting forward a factor that can be taken, namely demand factors, practical factors, and the profit factor so that these three factors can influence the existence of inaccuracies in the distribution of subsidized fuel oil. Inconsistency in the application of Law No. 11 of 2020 concerning copyright work on the crime of selling subsidized fuel oil is a phenomenon that has not been resolved by law enforcement in Dedai sub-district, Sintang Regency.